Fabry disease: An overlooked diagnosis in adult cardiac patients - Meral Kayıkçıoğlu; Evrim Şimşek; Sema Kalkan Uçar; Selen Bayraktaroğlu; Hüseyin Onay; Eser Sözmen; Mahmut Çoker (KARE Publishing, 2017)
Fabry disease is a rare, X-linked, lysosomal glycosphingolipid storage disorder. A deficiency of the enzyme alpha-galactosidase results in intracellular accumulation of globotriaosylceramide in multiple cell types, such as those of the nerves, kidneys, cardiac, and cutaneous tissues, leading to a multisystem disease. Male patients are more severely affected; however, heterozygous female patients may also be afflicted, though often the symptoms develop later. Cardiac involvement can include left ventricular hypertrophy, conduction abnormalities, arrhythmias, valvular abnormalities, and heart failure. A variant of the disease affects only cardiac tissue and mostly manifests as unexplained ventricular hypertrophy. Presently described are 2 cases of Fabry disease and the signs and symptoms of cardiac involvement, as well as the importance of early diagnosis to start enzyme replacement therapy before the development of irreversible tissue damage.